Does cognitive style affect bloggers’ attitude in an online learning environment? - Zahra Shahsavar,; Tan Bee Hoon, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
The prevalence of using blogs among college students has great impact in online communication. It is therefore important to identify how learners with different characteristics use this technology. This study examines if bloggers’ cognitive styles particularly field-dependency affects students’ attitudes toward blogs. The subjects were a class of undergraduate students enrolled in an obligatory course. The Group Embedded Figures Test was administered which classified them as either field dependent or field independent. Then, they were requested to respond to a questionnaire designed to assess their attitudes toward blogs on three factors: blog anxiety, blog desirability, and blog selfefficacy. Although field-dependents had lower blog anxiety, blog desirability, and blog self-efficacy than field-independents in using blogs, the difference was not statistically significant. Moreover, conclusions drawn from the interview questions support the notion that both field dependents and field independents appeared to have positive attitudes towards using blogs in a learning environment.